Customer-Based Brand Equity, Product Quality, Price and Customer Loyalty in Electronic Industry of Refrigerator - Bambang Suwarno (Publisher Cv. Inara, 2021)
The purpose of this study was to analyse the extent of Consumer-Based Brand Equity, Quality Product and Price affects customer loyalty at PT. Panasonic Gobel Indonesia Branch Medan and to compare the theories. The author examined by collecting data using a variety of library research, questionnaires are structured as an instrument to obtain quantitative data with Likert-scale systems are distributed to 68 respondents. Data was then compiled then processed and analysed using multiple regression analysis techniques (multiple regression) through the test of validity, test of reliability and test of classic assumptions. By using the tools of Statistical Product Service Solutions program (SPSS version 22.0). From the survey results revealed that the influential Consumer-Based Brand Equity, Product Quality and Price simultaneously with the results Fhitung 18,457 > Ftabel 2,75 and probability sig. 0,000 < 0,05 then reject ho (accept hi) that the Consumer-Based Brand Equity, Product Quality, Price simultaneously significantly influence Customer Loyalty PT. Panasonic Gobel Indonesia Branch Medan. The Consumer-Based Brand Equity there is for the partial influence on the Customer Loyalty with a value of thitung 3,980 > ttabel 1,997 and sig. 0,000 < 0,05, the Product Quality there is for the partial influence on the Customer Loyalty with a value of thitung 3,874 > ttabel 1,997 and sig. 0,000 < 0,05 and the Price there is for the partial influence on the Customer Loyalty with a value of thitung 2,483 > ttabel 1,997 and sig. 0,002 < 0,05. From the test results are also obtained by the value of determination R square is 0,564 or 56,4%. It is claimed that Consumer-Based Brand Equity, Product Quality and Price is an excellent way to improve Customer Loyalty and also the hypothesis that the authors proposed previously received.